Novel endosomal NOX2 oxidase inhibitor ameliorates pandemic influenza A virus‐induced lung inflammation in mice - To, Eunice E. (Respirology, 2019)
BACKGROUND AND OBJECTIVE: Influenza A viruses (IAV) cause respiratory tract infections that can be fatal when the virus spreads to the alveolar space (i.e. alveolitis), and this is mainly observed with highly pathogenic strains. Reactive oxygen species (ROS) production by the NOX2 NADPH oxidase in endosomes has been directly implicated in IAV pathology. Recently, we demonstrated that treatment with a novel endosome‐targeted NOX2 oxidase inhibitor, cholestanol‐conjugated gp91dsTAT (Cgp91ds‐TAT), attenuated airway inflammation and viral replication to infection with a low pathogenic influenza A viral strain. Here, we determined whether suppression of endosome NOX2 oxidase prevents the lung inflammation following infection with a highly pathogenic IAV strain. METHODS: C57Bl/6 mice were intranasally treated with either DMSO vehicle (2%) or Cgp91ds‐TAT (0.2 mg/kg/day) 1 day prior to infection with the high pathogenicity PR8 IAV strain (500 PFU/mouse). At Day 3 post‐infection, mice were culled for the evaluation of airway and lung inflammation, viral titres and ROS generation. RESULTS: PR8 infection resulted in a marked degree of airway inflammation, epithelial denudation, alveolitis and inflammatory cell ROS production. Cgp91ds‐TAT treatment significantly attenuated airway inflammation, including neutrophil influx, the degree of alveolitis and inflammatory cell ROS generation. Importantly, the anti‐inflammatory phenotype affected by Cgp91ds‐TAT significantly enhanced the clearance of lung viral mRNA following PR8 infection. CONCLUSION: Endosomal NOX2 oxidase promotes pathogenic lung inflammation to IAV infection. The localized delivery of endosomal NOX2 oxidase inhibitors is a novel therapeutic strategy against IAV, which has the potential to limit the pathogenesis caused during epidemics and pandemics.